Silica-aluminum material as well as preparation method and application thereof
By preparing silicon-aluminum materials with specific components and proportions, the synergistic effect of red mud, slag powder, silicate cement clinker, exciter and multiple expansion agents is used to form a dense crystal and amorphous interwoven structure, which solves the problems of large shrinkage and volume instability of silicon-aluminum gelling materials, and achieves high-strength and low shrinkage cement sand, enhancing the density and long-term stability of the material.
Patent Information
- Application Number
- CN202411838248.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2044-12-13
AI Technical Summary
The existing silicon-aluminum gelling materials have limited their wide application in the field of building materials due to their large shrinkage and volume instability.
By preparing a silicon-aluminum material, the material includes a specific proportion of red mud, slag powder, silicate cement clinker, exciter and expansion agent. The expansion agent contains at least two components, such as aluminum sulfate, calcium carbide slag, tricalcium aluminate, etc., through the synergistic action of these components, crystal phases such as ettringite and calcium hydroxide, and amorphous phases such as sodium aluminosilicate and calcium aluminosilicate, to construct a dense crystal and amorphous interwoven structure.
The silicon-aluminum material exhibits high strength and low shrinkage in cement sand, which enhances the compactness of the cement, prevents cracking, and ensures the stability of the material's long-term use.
Smart Images

Figure BDA0005187309370000111
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials, and specifically relates to a silicon-aluminum material and a preparation method and application thereof. Background Art
[0002] With the increasing concern about global warming and greenhouse gas emission reduction, the research and development of low-carbon technology has become an urgent need for the cement industry. In the past 20 years, different new low-carbon cementitious materials have been proposed by researchers. Among them, alkali-activated cementitious materials (also called AAS composite materials) have attracted widespread attention from researchers due to their outstanding characteristics such as low permeability, high strength, good thermal stability, excellent chemical corrosion resistance and dense microstructure. In addition, the precursor or raw material of the alkali-activated material is mainly industrial solid waste containing aluminosilicate glass, which can effectively reduce the greenhouse gas emissions released by the production of ordinary Portland cement (OPC), alleviate energy consumption, and have both economic sustainability and environmental friendliness.
[0003] Compared with traditional cement-based cementitious materials, although alkali-activated cementitious materials show excellent mechanical properties in construction, the shrinkage rate of alkali-activated cementitious materials is greater than that of ordinary silicate cement paste, and the volume instability limits the wide application of alkali-activated cementitious materials in the field of building materials. Due to its special depolymerization-polycondensation reaction mechanism, the hydration products and pore structures of silica-alumina cementitious materials are different from those of OPC. For example, compared with the amorphous hydration products such as sodium aluminosilicate hydrate and calcium aluminosilicate hydrate in silica-alumina cementitious materials and calcium silicate hydrate in OPC hydration products, the sodium aluminosilicate hydrate and calcium aluminosilicate hydrate in silica-alumina cementitious materials have higher specific surface areas and are more likely to shrink and deform when dehydrated and dried. In addition, the hydration products of silica-alumina cementitious materials lack crystalline phases such as Ca(OH)2, AFt and AFm with large elastic modulus and good volume stability. The above differences lead to large shrinkage rate and poorer volume stability of silica-alumina cementitious materials.
[0004] In recent years, although researchers have gradually paid attention to the hazards caused by shrinkage and actively studied various expansion agents, such as calcium sulfoaluminate expansion agents, calcium sulfoaluminate-calcium oxide expansion agents and calcium oxide expansion agents, due to their special reaction mechanism, hydration products and pore structure, the existing expansion agents cannot solve the problems of large shrinkage rate and poor volume stability of silica-alumina cementitious materials. Summary of the invention
[0005] Therefore, the technical problem to be solved by the present invention is to overcome the defects of existing silicon-aluminum gelling materials such as large shrinkage rate and poor volume stability, thereby providing a silicon-aluminum material and a preparation method and application thereof.
[0006] To this end, the present invention provides the following technical solutions:
[0007] The first aspect of the present invention protects a siliceous-aluminous material, wherein the siliceous-aluminous material comprises 10-65 parts by weight of red mud, 20-60 parts by weight of slag powder, 0-20 parts by weight of Portland cement clinker, 0.1-8 parts by weight of an activator and 5-15 parts by weight of an expansion agent;
[0008] Wherein, based on the mass of the expansion agent, the expansion agent includes 0-60wt% of aluminum sulfate, 0-70wt% of carbide slag, 0-70wt% of tricalcium aluminate, 0-60wt% of calcium sulfoaluminate, and 0-60wt% of gypsum, and the content of at least two components in the expansion agent is not zero.
[0009] In the present invention, the water content refers to the sum of physically adsorbed water and free water, excluding chemically bound water and crystallized water; the water content of the red mud, steel slag and slag powder is less than 1wt%.
[0010] In the present invention, the moisture content of the aluminum sulfate, tricalcium aluminate, carbide slag and calcium sulfoaluminate is less than 1wt%.
[0011] According to the present invention, the silicon-alumina material comprises 30-60 parts by weight of red mud, 35-55 parts by weight of slag powder, 5-15 parts by weight of Portland cement clinker, 3-5 parts by weight of an activator and 8-10 parts by weight of an expansion agent;
[0012] Wherein, based on the mass of the expansion agent, the expansion agent includes 0-50wt% of aluminum sulfate, 0-60wt% of carbide slag, 0-50wt% of tricalcium aluminate, 0-50wt% of calcium sulfoaluminate, and 0-50wt% of gypsum, and the content of at least two components in the expansion agent is not zero.
[0013] According to the present invention, based on the mass of the expander, the expander comprises 50 wt% of aluminum sulfate and 50 wt% of carbide slag.
[0014] According to the present invention, based on the mass of the expander, the expander comprises 40wt% of aluminum sulfate and 60wt% of carbide slag.
[0015] According to the present invention, based on the mass of the expansion agent, the expansion agent includes 50 wt % of tricalcium aluminate and 50 wt % of gypsum.
[0016] According to the present invention, based on the mass of the expansion agent, the expansion agent includes 50 wt% of calcium sulfoaluminate and 50 wt% of gypsum.
[0017] According to the present invention, based on the mass of the expansion agent, the expansion agent includes 30 wt% of aluminum sulfate, 30 wt% of carbide slag and 40 wt% of gypsum.
[0018] According to the present invention, the activator includes a calcium-containing activator and / or a sodium-containing activator; further, the activator includes at least one of calcium formate, calcium lignin sulfonate, sodium sulfate, calcium chloride, sodium carbonate, sodium hydroxide, and sodium silicate.
[0019] In the present invention, the activator is solid, contains water mainly in the form of crystal water and chemically bound water / hydroxyl group, and has a very low dosage, without the need for water control.
[0020] According to the present invention, the gypsum includes building gypsum. Typically, but not limitingly, the gypsum includes at least one of dihydrate gypsum, desulfurized gypsum, mirabilite gypsum, phosphogypsum, and titanium gypsum.
[0021] In the present invention, the gypsum contains crystal water in addition to physically adsorbed water and free water (the total water content of the two parts is estimated to be about 10%). However, the amount of gypsum used in the raw materials is relatively small, so the amount of water introduced into the grinding system is also very small and does not need to be specially controlled.
[0022] In the present invention, the red mud includes sintered red mud, which is conventional red mud in the art. Typically, but not limitingly, the red mud has an Al2O3 content of ≥6wt%, a SiO2 content of ≥10wt%, and a 28-day compressive strength activity index of higher than 60%.
[0023] In the present invention, the slag powder is conventional slag powder in the art, including water-quenched blast furnace slag powder and / or air-cooled blast furnace slag powder, and the water content of the slag powder is less than 1wt%.
[0024] In the present invention, the silicate cement clinker meets the requirements of GB / T 21372 "Silica cement clinker"; silicate cement clinker is a commercially available dry material, and typically, but not limitingly, the water content of silicate cement clinker is less than 1wt%.
[0025] According to the present invention, the water content of the silicon-aluminum material is less than 1 wt %.
[0026] According to the present invention, the average particle size of the silicon-aluminum material is 30-100 μm.
[0027] The second aspect of the present invention protects a method for preparing a silicon-aluminum material, wherein the components of the aforementioned silicon-aluminum material are homogenized, dried, and ground to obtain the silicon-aluminum material.
[0028] A third aspect of the present invention protects a cement mortar, wherein the cement mortar comprises the aforementioned silico-alumina material or the silico-alumina material prepared by the aforementioned preparation method.
[0029] In the present invention, under an environment of a temperature of 20±2°C and a relative humidity of ≥90%, the flexural strength of the cement mortar after curing in water for 3 days is greater than 7.0MPa, and the compressive strength is greater than 30.0MPa;
[0030] and / or, in an environment of a temperature of 20±2°C and a relative humidity of ≥90%, the flexural strength of the cement mortar after curing in water for 28 days is greater than 9.0 MPa, and the compressive strength is greater than 50.0 MPa;
[0031] And / or, the shrinkage rate of the product after curing in water for 28 days at a temperature of 20±2° C. and a relative humidity of 55±5% is × 10000<800%.
[0032] The technical solution of the present invention has the following advantages:
[0033] 1. The present invention provides a silicon-alumina material, wherein the silicon-alumina material comprises 10-65 parts by weight of red mud, 20-60 parts by weight of slag powder, 0-20 parts by weight of Portland cement clinker, 0.1-8 parts by weight of an activator and 5-15 parts by weight of an expansion agent; wherein, based on the mass of the expansion agent, the expansion agent comprises 0-60wt% of aluminum sulfate, 0-70wt% of carbide slag, 0-70wt% of tricalcium aluminate, 0-60wt% of calcium sulfoaluminate, and 0-60wt% of gypsum, and at least two components of the expansion agent are The content is not 0; the siliceous alumina material with specific components and contents of the present invention, under the action of an activator, red mud, slag powder, silicate cement clinker and part of the activator will form crystalline phases such as calcium aluminoferrite and calcium hydroxide and amorphous phases such as hydrated sodium aluminosilicate and hydrated calcium aluminosilicate, and the crystalline phase and the amorphous phase cooperate to construct the siliceous alumina material, in which the crystals are interspersed with the dense structure of the amorphous gel to improve the pore size distribution, so that when the siliceous alumina material is used in cement mortar, the cement mortar can have both high strength and low shrinkage, enhance the density of the cement and prevent cracking, so that the material can be used for a long time.
[0034] 2. In the present invention, the specific content of each component in the silicon-aluminum material increases the crystalline phase content, thereby further reducing the shrinkage degree and improving the mechanical properties.
[0035] 3. In the present invention, the specific combination of expansion agents can further reduce the degree of shrinkage, increase the stability of the matrix, and also improve the mechanical properties.
[0036] 4. In the present invention, each component in the silicon-aluminum material is first homogenized and then ground to ensure that the expansion agent is evenly distributed in the material and further reduce the shrinkage degree during subsequent use. DETAILED DESCRIPTION
[0037] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.
[0038] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0039] In order to facilitate comparison between data, the sources and compositions of red mud, Portland cement clinker and slag powder used in the following embodiments and comparative examples of the present invention are the same, and the specific contents of red mud, Portland cement clinker and slag powder are shown in Table 1;
[0040] Table 1
[0041] Red Mud Portland cement clinker Slag powder <![CDATA[Na2O eq .(wt%)]]> 3.29 0.22 0.46 MgO (wt%) 1.82 3.28 9.11 <![CDATA[Al2O3(wt%)]]> 8.58 4.11 16.32 <![CDATA[SiO2(wt%)]]> 19.73 18.77 30.52 <![CDATA[P2O5(wt%)]]> 0.24 0.08 0.02 <![CDATA[SO3(wt%)]]> 4.38 3.85 2.27 <![CDATA[K2O(wt%)]]> 0.09 0.88 0.4 CaO (wt%) 38.99 62.82 38.44 <![CDATA[TiO2(wt%)]]> 0.94 0.36 0.82 <![CDATA[V2O5(wt%)]]> 3.21 - - MnO (wt%) 0.04 0.06 0.52 <![CDATA[Fe2O3(wt%)]]> 7.78 3.36 0.31 Others (wt%) 0.79 0.24 0.12
[0042] The water content of aluminum sulfate is 0.1wt%;
[0043] The water content of tricalcium aluminate is 0.1wt%;
[0044] The water content of carbide slag is 0.1wt%;
[0045] The water content of calcium sulphoaluminate is 0.1wt%;
[0046] In the examples and comparative examples, 1 part by weight corresponds to 1 g.
[0047] Example 1
[0048] This embodiment provides a silicon-aluminum material, and the specific preparation method is as follows:
[0049] The silicoaluminous material comprises 60 parts by weight of red mud, 35 parts by weight of slag powder, 5 parts by weight of Portland cement clinker, 5 parts by weight of sodium hydroxide and 10 parts by weight of an expansion agent; the expansion agent comprises 50 wt% of aluminum sulfate and 50 wt% of carbide slag in terms of mass percentage of the expansion agent; all the components are homogenized, dried and ground to obtain the silicoaluminous material;
[0050] The water content of the silicon-aluminum material is 0.5wt%; and the average particle size of the silicon-aluminum material is 80μm.
[0051] Example 2
[0052] This embodiment provides a silicon-aluminum material, and the specific preparation method is as follows:
[0053] The silicoaluminous material comprises 30 parts by weight of red mud, 55 parts by weight of slag powder, 15 parts by weight of Portland cement clinker, 4 parts by weight of sodium hydroxide and 8 parts by weight of an expansion agent; the expansion agent comprises 40 wt% of aluminum sulfate and 60 wt% of carbide slag in terms of mass percentage of the expansion agent; all the components are homogenized, dried and ground to obtain the silicoaluminous material;
[0054] The water content of the silicon-aluminum material is 0.5wt%; and the average particle size of the silicon-aluminum material is 80μm.
[0055] Example 3
[0056] This embodiment provides a silicon-aluminum material, and the specific preparation method is as follows:
[0057] In the manner of Example 1, except that the expansion agent is 50wt% of tricalcium aluminate and 50wt% of dihydrate gypsum;
[0058] The water content of the silicon-aluminum material is 0.5wt%; and the average particle size of the silicon-aluminum material is 80μm.
[0059] Example 4
[0060] This embodiment provides a silicon-aluminum material, and the specific preparation method is as follows:
[0061] In the manner of Example 1, except that the expansion agent is 50wt% of calcium sulfoaluminate and 50wt% of dihydrate gypsum;
[0062] The water content of the silicon-aluminum material is 0.5wt%; and the average particle size of the silicon-aluminum material is 80μm.
[0063] Example 5
[0064] This embodiment provides a silicon-aluminum material, and the specific preparation method is as follows:
[0065] The silicoaluminous material comprises 65 parts by weight of red mud, 30 parts by weight of slag powder, 3 parts by weight of Portland cement clinker, 2 parts by weight of sodium hydroxide and 7 parts by weight of an expansion agent; the expansion agent comprises 50 wt% of aluminum sulfate and 50 wt% of carbide slag in terms of mass percentage of the expansion agent; all the components are homogenized, dried and ground to obtain the silicoaluminous material;
[0066] The water content of the silicon-aluminum material is 0.5wt%; and the average particle size of the silicon-aluminum material is 80μm.
[0067] Example 6
[0068] This embodiment provides a silicon-aluminum material, and the specific preparation method is as follows:
[0069] The method of Example 1 is the same, except that the expansion agent is 30wt% aluminum sulfate, 30wt% carbide slag and 40wt% dihydrate gypsum; the water content of the siliceous aluminum material is 0.5wt%; and the average particle size of the siliceous aluminum material is 80μm.
[0070] Example 7
[0071] This embodiment provides a silicon-aluminum material, and the specific preparation method is as follows:
[0072] The silicon-alumina material comprises 65 parts by weight of red mud, 35 parts by weight of slag powder, 5 parts by weight of sodium hydroxide and 10 parts by weight of an expander; the expander comprises 50 wt% of aluminum sulfate and 50 wt% of carbide slag in terms of mass percentage of the expander; all the components are homogenized, dried and ground to obtain the silicon-alumina material;
[0073] The water content of the silicon-aluminum material is 0.5wt%; and the average particle size of the silicon-aluminum material is 80μm.
[0074] Comparative Example 1
[0075] This comparative example provides a silicon-aluminum material, and the specific preparation method is as follows:
[0076] The silicoalumina material includes 60 parts by weight of red mud, 35 parts by weight of slag powder, 5 parts by weight of Portland cement clinker, and 5 parts by weight of sodium hydroxide. All the components are homogenized, dried, and ground to obtain the silicoalumina material;
[0077] The water content of the silicon-aluminum material is 0.5wt%; and the average particle size of the silicon-aluminum material is 80μm.
[0078] Comparative Example 2
[0079] This comparative example provides a silicon-aluminum material, and the specific preparation method is as follows:
[0080] The silicoaluminous material comprises 70 parts by weight of red mud, 5 parts by weight of slag powder, 25 parts by weight of silicate cement clinker, 10 parts by weight of sodium hydroxide and 10 parts by weight of an expansion agent; the expansion agent comprises 50 wt% of aluminum sulfate and 50 wt% of carbide slag in terms of mass percentage of the expansion agent; all the components are homogenized, dried and ground to obtain the silicoaluminous material;
[0081] The water content of the silicon-aluminum material is 0.5wt%; and the average particle size of the silicon-aluminum material is 80μm.
[0082] Comparative Example 3
[0083] This comparative example provides a silicon-aluminum material, and the specific preparation method is as follows:
[0084] The method of Example 1 is different in that the expansion agent is aluminum sulfate; all components are homogenized, dried, and ground to obtain a silicon-aluminum material;
[0085] The water content of the silicon-aluminum material is 0.5wt%; and the average particle size of the silicon-aluminum material is 80μm.
[0086] Comparative Example 4
[0087] This comparative example provides a silicon-aluminum material, and the specific preparation method is as follows:
[0088] The method of Example 1 is different in that the expansion agent is carbide slag; all components are homogenized, dried, and ground to obtain a silicon-aluminum material;
[0089] The water content of the silicon-aluminum material is 0.5wt%; and the average particle size of the silicon-aluminum material is 80μm.
[0090] Test Case
[0091] The silicon-aluminum materials prepared in the embodiment and the comparative example were mixed and molded according to the provisions of GB / T176711999 "Test Method for Strength of Cement Mortar (ISO Method)", wherein the test specimens were prepared by mass, one part of silicon-aluminum material and three parts of Chinese ISO standard sand, with a water-cement ratio of 0.5, and prepared into prism specimens with a size of 40mm×40mm×160mm in width×height×length, and cured in water: the mortar specimens were demolded after being cured in a curing box at 20±2°C and relative humidity ≥90% for 1 day, and the demolded specimens were placed in water at 20±1°C for curing for 3 days and 28 days, and then the flexural strength and compressive strength were tested;
[0092] The specimens for drying shrinkage test were prepared according to JC / T 603-2004 "Test Method for Drying Shrinkage of Cement Mortar". The specimens were measured by mass, one part of silicon-aluminum material and two parts of Chinese ISO standard sand, and prepared into mortar specimens with a size of 25mm×25mm×280mm. After demolding, they were directly placed in an environment with a temperature of 20±2℃ and a relative humidity of 55±5%, and tested after curing for the specified 3 days and 28 days. Taking the 28-day age as an example, the drying shrinkage of the cement mortar specimen at 28d age was calculated according to the following formula: S 28 =(L0-L 28 )×100 / 250;
[0093] In the formula: S 28 It is the shrinkage rate of cement mortar at 28 days, in percentage (%);
[0094] L0 is the initial measurement reading in millimeters (mm);
[0095] L 28 The readings are measured at 28 days old, in millimeters (mm);
[0096] 250 is the effective length of the specimen, in millimeters (mm);
[0097] The specific test results are shown in Table 2.
[0098] Table 2
[0099]
[0100]
[0101] The silicon-aluminum material prepared by the composition of the specific components and dosage of the present invention can achieve both high strength and low shrinkage. When used in cement mortar, it can enhance the density of cement and prevent cracking, so that the material can be used for a long time.
[0102] Comparison of Example 1, Example 3-4, and Example 6 shows that specific combinations of specific types of expansion agents reduce the degree of shrinkage and increase the stability of the matrix.
[0103] Comparing Example 1 with Example 5, it can be seen that the specific content of each component in the composition can further reduce the shrinkage degree and improve the mechanical properties.
[0104] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.
Claims
1. A silicon-aluminum material, characterized in that: The siliceous-aluminous material comprises 10-65 parts by weight of red mud, 20-60 parts by weight of slag powder, 0-20 parts by weight of Portland cement clinker, 0.1-8 parts by weight of an activator and 5-15 parts by weight of an expansion agent; Wherein, based on the mass of the expansion agent, the expansion agent includes 0-60wt% of aluminum sulfate, 0-70wt% of carbide slag, 0-70wt% of tricalcium aluminate, 0-60wt% of calcium sulfoaluminate, and 0-60wt% of gypsum, and the content of at least two components in the expansion agent is not zero.
2. The silicon-aluminum material according to claim 1, characterized in that: The siliceous-aluminous material comprises 30-60 parts by weight of red mud, 35-55 parts by weight of slag powder, 5-15 parts by weight of Portland cement clinker, 3-5 parts by weight of an activator and 8-10 parts by weight of an expansion agent; Wherein, based on the mass of the expansion agent, the expansion agent includes 0-50wt% of aluminum sulfate, 0-60wt% of carbide slag, 0-50wt% of tricalcium aluminate, 0-50wt% of calcium sulfoaluminate, and 0-50wt% of gypsum, and the content of at least two components in the expansion agent is not zero.
3. The silicon-aluminum material according to claim 1, characterized in that: The expander comprises 50wt% aluminum sulfate and 50wt% carbide slag based on the mass of the expander; and / or, based on the mass of the expander, the expander comprises 40wt% aluminum sulfate and 60wt% carbide slag; and / or, based on the mass of the expansion agent, the expansion agent comprises 50wt% tricalcium aluminate and 50wt% gypsum; and / or, based on the mass of the expansion agent, the expansion agent comprises 50 wt% of calcium sulfoaluminate and 50 wt% of gypsum; And / or, based on the mass of the expansion agent, the expansion agent includes 30 wt% of aluminum sulfate, 30 wt% of carbide slag and 40 wt% of gypsum.
4. The silicon-aluminum material according to any one of claims 1 to 3, characterized in that: The stimulant includes a calcium-containing stimulant and / or a sodium-containing stimulant.
5. The silicon-aluminum material according to claim 4, characterized in that: The activator includes at least one of calcium formate, calcium lignin sulfonate, sodium sulfate, calcium chloride, sodium carbonate, sodium hydroxide, and sodium silicate.
6. The silicon-aluminum material according to any one of claims 1 to 5, characterized in that: The gypsum includes at least one of dihydrate gypsum, desulfurized gypsum, mirabilite gypsum, phosphogypsum and titanium gypsum.
7. The silicon-aluminum material according to any one of claims 1 to 6, characterized in that: The water content of the silicon-aluminum material is less than 1 wt %.
8. The silicon-aluminum material according to any one of claims 1 to 7, characterized in that: The average particle size of the silicon-aluminum material is 30-100 μm.
9. A method for preparing a silicon-aluminum material, characterized in that: The components of the silicon-aluminum material according to any one of claims 1 to 5 are homogenized, dried, and ground to obtain the silicon-aluminum material.
10. A cement mortar, characterized in that: The cement mortar comprises the silicon-aluminum material described in any one of claims 1 to 8 or the silicon-aluminum material prepared by the preparation method described in claim 9.
Citation Information
Patent Citations
Low-shrinkage alkali-activated cementing material and preparation method thereof
CN116589233A
Cement and preparation method thereof
CN117383846A
Silica-aluminum cementing material shrinkage reducing agent as well as preparation method and application thereof
CN118388162A
Cement admixture
JP2022183540A
Dimensionally stable geopolymer composition and method
WO2013163009A1
Cited By
High-strength low-carbon cementing material regulated and controlled through pH value as well as preparation method and application of high-strength low-carbon cementing material
CN120398449A